PENYULUHAN PADA IBU DAN PEMBERIAN MAKANAN BERGIZI UNTUK PENCEGAHAN STUNTING PADA ANAK - Efi Irwansyah Pane; Joni Siagian; Amelia Dini Anggraini Silalah (Jurnal Pengabdian Keperawatan Dan Kesehatan Holistik, 2025)
Stunting is a chronic nutritional problem that affects children's physical growth and cognitive development. The main cause of stunting is a lack of adequate nutritional intake from pregnancy to the age of two. This community service activity aims to increase mothers' knowledge about stunting and the importance of providing nutritious food in preventing it. This activity was carried out in Binjai Serbangan Village, Air Joman District, targeting mothers who have toddlers. The method used was counseling and demonstration of providing nutritious food using local food ingredients. A total of 45 mothers participated in this activity. The evaluation results showed an increase in participants' knowledge by 78% after the counseling. This activity succeeded in increasing mothers' understanding of the importance of a healthy diet and balanced nutrition for children. It is hoped that this activity can contribute to reducing stunting rates in the area. Active community involvement and cross-sectoral cooperation are very important in efforts to prevent stunting sustainably.